Building sustainability, nutritional and livelihood security in India through dairying: A situational analysis in G20 perspective - Maiti, Sanjit; Zade, Siddhesh; Panja, Amitava; Garai, Sanchita; Singh, R K (Indian Farming, 2023)
Dairying is an imperative agricultural enterprise undertaken by a majority of agrarian communities in India forming a backbone for supporting livelihood and nutritional security in a sustainable manner. Dairying provides a path towards developing integrated farming systems with minimal losses and optimum utilization of various resources. Thus, providing year-round employment (especially for women) and steady income thereby supporting the livelihood which in turn leads to women empowerment and paves the way for gender equality. Yet it has a challengingly long way to go ahead in terms of improving the per capita availability and export of milk. This requires improvement in quality and quantity so that the profitability of the venture may increase which can be achieved through intervention of G20, as it underpins agriculture and climate change as focus areas. Thus, it can serve as a powerful instrument for the alleviation of Indian agriculture in general and dairying in particular in terms of productivity and marketing at the global level by a conglomeration of various stakeholders at national as well as international levels who may be motivated to undertake climate-resilient dairy practices to improve dairying with minimal impact on climate.